Similarities and differences in the neural correlates of letter and speech sound integration in blind and sighted readers - Beck, Joanna; Dzięgiel-Fivet, Gabriela; Jednoróg, Katarzyna (NeuroImage (Orlando, Fla.), 2023)
•The neural basis of letter-speech sound (LS) integration is similar in the blind and sighted.•In both groups the integration takes place in the superior temporal cortex.•The direction of the congruency effect is different between the groups.•LS discrimination efficiency and congruency effect correlated with age and reading skills only in the sighted. Learning letter and speech sound (LS) associations is a major step in reading acquisition common for all alphabetic scripts, including Braille used by blind readers. The left superior temporal cortex (STC) plays an important role in audiovisual LS integration in sighted people, but it is still unknown what neural mechanisms are responsible for audiotactile LS integration in blind individuals. Here, we investigated the similarities and differences between LS integration in blind Braille (N = 42, age range: 9–60 y.o.) and sighted print (N = 47, age range: 9–60 y.o.) readers who acquired reading using different sensory modalities. In both groups, the STC responded to both isolated letters and isolated speech sounds, showed enhanced activation when they were presented together, and distinguished between congruent and incongruent letter and speech sound pairs. However, the direction of the congruency effect was different between the groups. Sighted subjects showed higher activity for incongruent LS pairs in the bilateral STC, similarly to previously studied typical readers of transparent orthographies. In the blind, congruent pairs resulted in an increased response in the right STC. These differences may be related to more sequential processing of Braille as compared to print reading. At the same time, behavioral efficiency in LS discrimination decisions and the congruency effect were found to be related to age and reading skill only in sighted participants, suggesting potential differences in the developmental trajectories of LS integration between blind and sighted readers.